Romania : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2002 Article IV Consultation highlights that since mid-2001, a combination of budget restraint, ambitious energy price adjustments, and prudent monetary policy moderated domestic demand and reduced the current account deficit in Romania. At the same time, export and GDP growth were among the highest in the region, reflecting the fruits of private investments in export-oriented consumer goods industries over the last few years, and the gains in competitiveness from the 1999 adjustment in the real effective exchange rate. Rising productivity, complemented by moderate economy-wide wage growth, has preserved competitiveness.